Interactive virtual try-on based three-dimensional garment block design for disabled people of scoliosis type. Issue 10 (June 2017) - Hong, Yan; Zeng, Xianyi; Bruniaux, Pascal; Liu, Kaixuan
This paper introduces a co-design-based method for generating two-dimensional (2D) block patterns for physically disabled people with scoliosis, using three-dimensional (3D) virtual technology. A parameterization process is first performed on a scanned 3D body for creating a digitalized model of the human body, permitting simulation of the consumer's morphological shape with atypical physical deformations. Feature points of the human body for designing a garment block are discussed and classified with wearing ease for obtaining a desired fit effect based on the parameterized model. A basic garment block wire-frame aligned with body features is then established based on the defined feature points of the human body. Based on the deformed wireframe, a 3D expandable garment block is modeled. Customized 2D and 3D virtual garment prototyping tools are applied to create customized garment products based on the general concept of co-design by running the sequence Design–Display–Evaluation–Adjustment using the garment design process and design knowledge, which have already been applied to normal body shapes successfully. Through this process, the classical 2D garment design knowledge, especially 2D pattern design rules, will be modified according to the virtual garment evaluation procedure. The proposed method is validated and compared with the conventional block patternmaking methods in the virtual environment. The experimental results show that the proposed method is easier to implement and can generate garment patterns with satisfactory fit. Furthermore, the method can be used to create fit-ensured mass-customized apparel products (the top body type) for disabled people with scoliosis.